How glycosylation affects glycosylation: the role of N-glycans in glycosyltransferase activity. (4th May 2020) - Mikolajczyk, Krzysztof; Kaczmarek, Radoslaw; Czerwinski, Marcin
Abstract: N-glycosylation is one of the most important posttranslational modifications of proteins. It plays important roles in the biogenesis and functions of proteins by influencing their folding, intracellular localization, stability and solubility. N-glycans are synthesized by glycosyltransferases, a complex group of ubiquitous enzymes that occur in most kingdoms of life. A growing body of evidence shows that N-glycans may influence processing and functions of glycosyltransferases, including their secretion, stability and substrate/acceptor affinity. Changes in these properties may have a profound impact on glycosyltransferase activity. Indeed, some glycosyltransferases have to be glycosylated themselves for full activity. N-glycans and glycosyltransferases play roles in the pathogenesis of many diseases (including cancers), so studies on glycosyltransferases may contribute to the development of new therapy methods and novel glycoengineered enzymes with improved properties. In this review, we focus on the role of N-glycosylation in the activity of glycosyltransferases and attempt to summarize all available data about this phenomenon.